Budgeting and Cost Analysis for Hospital Management (Book). - Zeff, Stephen A.; Rorem, C. Rufus (The Accounting Review, 1964)
Reviews the book "Budgeting and Cost Analysis for Hospital Management," by Leon E. Hay.